Engaging future educators: Perceptions of project-based learning among pre-service EYL teachers - Soviyah, Soviyah (English Language Teaching Educational Journal, 2023)
In a globalized era with very rapid changes in life nowadays, project-based learning is considered as one of the most suitable learning models. Project-based learning provides learning that develops students' skills in communication, collaboration, critical thinking, and creativity. Therefore, EYL teacher education programs should provide opportunities for pre-service EYL teachers to improve their knowledge and skills in project-based learning. The purpose of this study was to determine pre-service EYL teachers' perceptions of project-based learning and its implementation. Conducted in 2022/2023, a total of 55 pre-service EYL teachers from TEYL PD   course who were purposively selected participated in this study. Data were collected using a 25-item perception of project-based learning scale. Descriptive quantitative analysis was used to analyze the data. The results showed that out of 55 student respondents, 18 respondents (33%) had a very positive perception, 33 respondent (60%) had a positive perception, 4 respondents (7%) had a neutral perception, and no respondents had a negative perception.